1989
DOI: 10.1159/000138622
|View full text |Cite
|
Sign up to set email alerts
|

Modes of Association of Indometacin with Human Polymorphonuclear Leucocytes

Abstract: The basic transport properties of indometacin (INDO) were investigated in human blood polymorphonuclear leucocytes (PMNs) of healthy volunteers. The silicone oil cushion centrifugation method was used as ligand-binding assay for both the measurements of the cellular association of INDO and the intracellular volume. This assay enabled us to calculate the intracellular INDO concentrations. A considerable amount of INDO accumulates in the PMNs to cause cell/medium ratios between 20 and 90. At low INDO levels (1–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0
2

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
2
1
0
2
Order By: Relevance
“…There are only a few reports on the binding affinities of other NSAIDs to PMNs. Raghoebar reported that indomethacin was rapidly taken up by the cells, reaching a steady state after 30 min [12], which is consistent with the rapid cell binding of SFP observed in our study. However, it remained unclear in our binding study as to whether the SFP was incorporated into the cells or not.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There are only a few reports on the binding affinities of other NSAIDs to PMNs. Raghoebar reported that indomethacin was rapidly taken up by the cells, reaching a steady state after 30 min [12], which is consistent with the rapid cell binding of SFP observed in our study. However, it remained unclear in our binding study as to whether the SFP was incorporated into the cells or not.…”
Section: Discussionsupporting
confidence: 92%
“…The whole cell was kept at 37˚C and stirred using a magnetic stirrer. An aliquot of the receiver solution was collected as the sample at determined times (4,6,8,10,12 and 24 h). The concentrations of SFP and RFP in the samples were determined by HPLC.…”
Section: In Vitro Skin Permeation Studymentioning
confidence: 99%
“…Higher leukocytes and lymphocytes counts were also associated with higher HCQ blood levels in our cSLE patients. These findings had already been reported in the adult population, possibly indicating the role of these immune cells as targets for drug accumulation and transport to inflamed tissues 24,25 .…”
Section: Discussionsupporting
confidence: 70%
“…Estudos em animais e humanos demonstraram ainda que o estado de equilíbrio da concentração de HCQ nos diferentes tecidos e no plasma é atingido após três meses de tratamento (Browning, 2014). Além disso, a aplicação de critérios de exclusão rigorosos foi importante para evitar fatores de confusão devido a interações medicamentosas (McElnay et al, 1985;Munster et al, 2002;Browning, 2014;Melles & Marmor, 2014;Jallouli et al, 2015;Baburaj et al, 2021), bem como infecções atuais, insuficiências hepática, cardíaca e renal grave (Raghoebar et al, 1986;Schrezenmeier & Dörner, 2020).…”
Section: Discussionunclassified
“…insuficiências hepática e cardíaca (Raghoebar et al, 1986;Schrezenmeier & Dörner, 2020); diálise, insuficiência renal crônica grave (creatinina sérica ≥ 3 mg/dL) (AbuRahma et al, 2014;Schrezenmeier & Dörner, 2020); gestação; e recusa em participar do estudo. A adesão ao tratamento foi avaliada por meio dos dados eletrônicos de refil de farmácia (RF) disponíveis no sistema de dispensação de medicamentos da farmácia institucional.…”
Section: Critérios De Exclusãounclassified